ISOTERM ADSORPSI Pb(II) PADA KARBON AKTIF TEMPURUNG KELAPA DENGAN VARIASI KONSENTRASI AKTIVATOR NATRIUM BIKARBONAT (ISOTHERMAL ADSORPTION OF Pb(II) BY ACTIVATED CARBON WITH VARIATIONS IN CONCENTRATION OF SODIUM BICARBONATE) - Erma Maruni; Nurlina Nurlina; Nelly Wahyuni (Tanjungpura University, 2022)
ABSTRACT Activated carbon is a porous solid that contains 85-95% carbon. The study used coconut shells as carbon sources and sodium bicarbonate as activators. Sodium bicarbonate can release carbon dioxide (CO2), where the CO2 will be used as a carbon donor. The study aims to explain the properties of carbon, activated carbon (KA) and its performance test in the solutions of Pb(II) ions. Metallic lead is toxic, which can slow down the normal working of red blood cells so that it can cause anaemia and can also inhibit the biosynthesis of haemoglobin. The research phase starts from the pyrolysis of coconut shells (t =2 hours, T=230 oC) to carbon. Carbon is activated with the variated percentage of sodium bicarbonate from 0 % to 8% and soaked for 24 hours (KA 0%, KA 4% and KA 8%). Activated carbon is characterized by water content, ash content, uptake of iodine, and methylene blue following the SNI method. Carbon, KA 0%, KA 4% and KA 8% tested its performance as adsorbent ion Pb(II) from PbNO3 solution with concentrations of 5, 10, 15, 20 and 25 ppm. The results showed that the water content, ash levels, and uptake of blue methylene KA met SNI No. 06-3730-1995. The highest adsorption efficiency at five ppm Pb(II) of carbon = 86.87%, KA 4% = 99.01% Isotherm adsorption of Pb(II) ions fitted to Langmuir for Carbon and KA 4% with K = 1.5044 L/g, am = 0.11 mg/g and K= 4.9468 L/g, am = 1.0735 mg/g, respectively